Stacked body and method for manufacturing stacked body

CN120112421BActive Publication Date: 2026-11-03ZEON CORP
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202480004568.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2023-03-27
Filing Date
2024-03-05
Publication Date
2026-11-03
Estimated Expiration
2044-03-05

AI Technical Summary

Technical Problem

Existing laminates of vinyl chloride resin molded parts and foamed polyurethane molded parts are prone to discoloration, especially yellowing, under high temperature conditions.

Method used

A vinyl chloride resin composition comprising vinyl chloride resin, aliphatic dicarboxylate, and plasticizer is used. The vinyl chloride resin molded body and the foamed polyurethane molded body are stacked adjacently. The aliphatic dicarboxylate can deactivate the amine component under high temperature conditions, prevent hydrogen chloride from being released, and thus inhibit the discoloration of the vinyl chloride resin molded body.

Benefits of technology

It effectively inhibits the discoloration of vinyl chloride resin molded parts under high temperature conditions, while improving the powder flowability, softness, light resistance and surface smoothness of vinyl chloride resin compositions, making it suitable for automotive interior materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005374329070000191
    Figure BDA0005374329070000191
  • Figure BDA0005374329070000201
    Figure BDA0005374329070000201
  • Figure BDA0005374329070000211
    Figure BDA0005374329070000211
Patent Text Reader

Abstract

The present invention provides a laminate of a vinyl chloride resin molded body and a foamed polyurethane molded body, which suppresses discoloration of the vinyl chloride resin molded body under high temperature conditions. The laminate of the present invention has a vinyl chloride resin molded body and a foamed polyurethane molded body laminated adjacent to the vinyl chloride resin molded body, the vinyl chloride resin molded body being a molded body formed by molding a vinyl chloride resin composition containing a vinyl chloride resin, an aliphatic dicarboxylic acid salt, and a plasticizer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to laminates and methods for manufacturing laminates. Background Technology

[0002] Vinyl chloride resin is commonly used in various applications due to its excellent properties such as cold resistance, heat resistance, and oil resistance. For example, in the formation of automotive interior parts such as dashboards and door trims, laminates are made by stacking vinyl chloride resin molded bodies with foamed polyurethane molded bodies adjacent to each other. Moreover, the technology for manufacturing such laminates has been under continuous research.

[0003] For example, in Patent Document 1, a vinyl chloride resin composition containing: vinyl chloride resin; plasticizer; hydrotalcite-based stabilizer, zeolite-based stabilizer and β-diketone additives is powdered to prepare a vinyl chloride resin molded body, and a foamed polyurethane molded body is laminated on the vinyl chloride resin molded body to produce a laminated body.

[0004] Existing technical documents

[0005] Patent documents

[0006] Patent Document 1: International Publication No. 2020 / 090556. Summary of the Invention

[0007] The problem the invention aims to solve

[0008] Here, the existing laminates of vinyl chloride resin molded articles and foamed polyurethane molded articles, including those in Patent Document 1 mentioned above, have the problem that the vinyl chloride resin molded articles will discolor (especially yellow) when exposed to high temperature conditions. That is, there is room for improvement in the existing laminates in suppressing the discoloration of vinyl chloride resin molded articles under high temperature conditions.

[0009] Therefore, the object of the present invention is to provide a laminate of a vinyl chloride resin molded body and a foamed polyurethane molded body that suppresses discoloration of the vinyl chloride resin molded body under high temperature conditions, and a method for manufacturing the laminate.

[0010] Solution for solving the problem

[0011] The inventors conducted in-depth research with the aim of solving the above-mentioned problems. Then, the inventors discovered that when manufacturing vinyl chloride resin molded articles constituting laminates, if a vinyl chloride resin composition containing aliphatic dicarboxylate in addition to vinyl chloride resin and plasticizer is used, discoloration of the vinyl chloride resin molded articles under high-temperature conditions can be suppressed, thus completing the present invention.

[0012] That is, the purpose of the present invention is to advantageously solve the above-mentioned problems. According to the present invention, a method for manufacturing the laminates of [1] to [6] and the laminates of [7] to

[12] can be provided.

[0013] [1] A laminate having a vinyl chloride resin molded body and a foamed polyurethane molded body stacked adjacent to the vinyl chloride resin molded body, wherein the vinyl chloride resin molded body is a molded body formed by molding a vinyl chloride resin composition comprising vinyl chloride resin, aliphatic dicarboxylate and plasticizer.

[0014] A molded body comprising a vinyl chloride resin composition, an aliphatic dicarboxylate, and a plasticizer, i.e. a laminate of a vinyl chloride resin molded body and a foamed polyurethane molded body, is not prone to discoloration when exposed to high temperature conditions.

[0015] [2] According to the laminate described in [1] above, the content of the aliphatic dicarboxylic acid salt in the vinyl chloride resin composition is 0.30 parts by mass or more and 8.00 parts by mass or less relative to 100 parts by mass of the vinyl chloride resin.

[0016] If the content of aliphatic dicarboxylate in the vinyl chloride resin composition is within the above-mentioned range, discoloration under high-temperature conditions can be further suppressed for the vinyl chloride resin molded articles constituting the laminate. Furthermore, when making vinyl chloride resin molded articles from the vinyl chloride resin composition, the powder flowability of the vinyl chloride resin composition can be improved.

[0017] [3] According to the laminate described in [1] or [2] above, wherein the aliphatic dicarboxylate contains at least one selected from disodium maleate, disodium malonate, disodium succinate, disodium adipate and disodium sebacate.

[0018] If any of the above-mentioned components are used as aliphatic dicarboxylate salts, discoloration under high-temperature conditions can be further suppressed in vinyl chloride resin molded articles constituting laminates. Furthermore, when making vinyl chloride resin molded articles from vinyl chloride resin compositions, the powder flowability of the vinyl chloride resin composition can be improved.

[0019] [4] The laminate according to any one of [1] to [3] above, wherein the content of the plasticizer in the vinyl chloride resin composition is 50 parts by mass or more and 200 parts by mass or less relative to 100 parts by mass of the vinyl chloride resin.

[0020] If the content of plasticizer in the vinyl chloride resin composition is within the above-mentioned range, the softness and light resistance of the vinyl chloride resin molded article constituting the laminate can be improved. Furthermore, when making a vinyl chloride resin molded article from the vinyl chloride resin composition, the powder flowability of the vinyl chloride resin composition can be improved. Additionally, the surface smoothness of the vinyl chloride resin molded article can be improved while simultaneously increasing the meltability of the vinyl chloride resin composition.

[0021] [5] The laminate according to any one of [1] to [4] above, wherein the plasticizer comprises polyester, the polyester containing structural units derived from dioxic acid and structural units derived from polyol.

[0022] Using polyester as a plasticizer can improve the lightfastness and heat shrinkage resistance of the vinyl chloride resin molded articles constituting the laminate. Furthermore, when making vinyl chloride resin molded articles from the vinyl chloride resin composition, the powder flowability of the vinyl chloride resin composition can be improved. Additionally, the surface smoothness of the vinyl chloride resin molded articles can be improved while simultaneously increasing the meltability of the vinyl chloride resin composition.

[0023] [6] The laminate described in any one of [1] to [5] above, wherein the laminate is used in an automotive dashboard.

[0024] [7] A method for manufacturing a laminate includes the following steps: molding a vinyl chloride resin composition comprising vinyl chloride resin, an aliphatic dicarboxylate and a plasticizer to obtain a vinyl chloride resin molded body; and laminating a foamed polyurethane molded body onto the surface of the vinyl chloride resin molded body to obtain a laminate in which the vinyl chloride resin molded body and the foamed polyurethane molded body are laminated adjacent to each other.

[0025] A laminate of vinyl chloride resin molded body and foamed polyurethane molded body obtained by molding a vinyl chloride resin composition containing vinyl chloride resin, aliphatic dicarboxylate and plasticizer is not prone to discoloration when exposed to high temperature conditions.

[0026] [8] In the method for manufacturing the laminate described in [7] above, the content of the aliphatic dicarboxylic acid salt in the vinyl chloride resin composition is 0.30 parts by mass or more and 8.00 parts by mass or less relative to 100 parts by mass of the vinyl chloride resin.

[0027] If the content of aliphatic dicarboxylate in the vinyl chloride resin composition is within the above-mentioned range, then the discoloration under high-temperature conditions can be further suppressed for the vinyl chloride resin molded articles constituting the laminate. Furthermore, when making vinyl chloride resin molded articles from the vinyl chloride resin composition, the powder flowability of the vinyl chloride resin composition can be improved.

[0028] [9] The method for manufacturing the laminate as described in [7] or [8] above, wherein the aliphatic dicarboxylic acid salt comprises at least one selected from disodium maleate, disodium malonate, disodium succinate, disodium adipate and disodium sebacate.

[0029] If any of the above is used as an aliphatic dicarboxylate, discoloration under high-temperature conditions can be further suppressed for the vinyl chloride resin molded articles constituting the laminate. Furthermore, when making vinyl chloride resin molded articles from the vinyl chloride resin composition, the powder flowability of the vinyl chloride resin composition can be improved.

[0030]

[10] In the method for manufacturing the laminate according to any one of [7] to [9] above, the content of the plasticizer in the vinyl chloride resin composition is 50 parts by mass or more and 200 parts by mass or less relative to 100 parts by mass of the vinyl chloride resin.

[0031] If the content of plasticizer in the vinyl chloride resin composition is within the above-mentioned range, the softness and light resistance of the vinyl chloride resin molded article constituting the laminate can be improved. Furthermore, when making a vinyl chloride resin molded article from the vinyl chloride resin composition, the powder flowability of the vinyl chloride resin composition can be improved. Additionally, the surface smoothness of the vinyl chloride resin molded article can be improved while simultaneously increasing the meltability of the vinyl chloride resin composition.

[0032]

[11] The method for manufacturing a laminate according to any one of [7] to

[10] above, wherein the plasticizer comprises a polyester, the polyester containing structural units derived from dioxic acid and structural units derived from polyols.

[0033] Using the aforementioned polyester as a plasticizer can improve the lightfastness and heat shrinkage resistance of the vinyl chloride resin molded articles constituting the laminate. Furthermore, when making vinyl chloride resin molded articles from the vinyl chloride resin composition, the powder flowability of the vinyl chloride resin composition can be improved. Additionally, the surface smoothness of the vinyl chloride resin molded articles can be improved while simultaneously increasing the meltability of the vinyl chloride resin composition.

[0034]

[12] The method for manufacturing the laminate according to any one of [7] to

[11] above, wherein the above-mentioned vinyl chloride resin composition powder is slush molded to obtain the above-mentioned vinyl chloride resin molded body.

[0035] If a vinyl chloride resin composition powder is slush molded to produce a vinyl chloride resin molded body, it is easy to obtain a vinyl chloride resin molded body that can be well used as an automotive interior material, such as a dashboard cover for automobiles.

[0036] Invention Effects

[0037] According to the present invention, a laminate of a vinyl chloride resin molded body and a foamed polyurethane molded body that suppresses discoloration of the vinyl chloride resin molded body under high temperature conditions can be provided, as well as a method for manufacturing the laminate. Detailed Implementation

[0038] The embodiments of the present invention will now be described in detail.

[0039] The laminate of the present invention is suitable for use as an automotive interior material in the manufacture of automotive interior components such as automotive dashboards and door trims. Furthermore, the manufacturing method of the laminate of the present invention can be used in the manufacture of the laminate of the present invention.

[0040] (Layered structure)

[0041] The laminate of the present invention is formed by stacking adjacent vinyl chloride resin molded bodies and polyurethane foam molded bodies. The vinyl chloride resin molded body typically constitutes one surface of the laminate. Alternatively, the laminate may have any structure other than the vinyl chloride resin molded body and the polyurethane foam molded body, depending on its application.

[0042] Furthermore, in the laminate of the present invention, a vinyl chloride resin molded body is formed from a vinyl chloride resin composition comprising vinyl chloride resin, aliphatic dicarboxylate and plasticizer, so the vinyl chloride resin molded body is not prone to discoloration when exposed to high temperature conditions.

[0043] The reason why the discoloration of the vinyl chloride resin molded body can be suppressed when the laminate is exposed to high temperature conditions by molding the vinyl chloride resin composition as described above is not clear, but it is speculated as follows.

[0044] First, amine components, used as polymerization catalysts, sometimes remain in polyurethane foam molded articles. In laminates of vinyl chloride resin molded articles and polyurethane foam molded articles, especially under high-temperature conditions, these amine components sometimes migrate from the polyurethane foam molded article to the vinyl chloride resin molded article. Furthermore, research by the inventors has shown that hydrogen chloride is released from the vinyl chloride resin due to reaction with the amine components, and this hydrogen chloride is a cause of discoloration in the vinyl chloride resin molded article. In contrast, in the laminate of the present invention, since the vinyl chloride resin molded article contains an aliphatic dicarboxylate from the vinyl chloride resin composition, the aliphatic dicarboxylate can deactivate the amine components. In particular, the aliphatic dicarboxylate has two carboxylic acid groups instead of one, thus enabling it to firmly capture the amine components through the cross-linking structure of the carboxylic acid groups. Therefore, it is believed that the release of hydrogen chloride from the vinyl chloride resin caused by the amine components can be suppressed, preventing discoloration of the vinyl chloride resin molded article.

[0045] <Molded body of vinyl chloride resin>

[0046] A vinyl chloride resin molded body is a molded body of a vinyl chloride resin composition.

[0047] Here, the vinyl chloride resin composition includes vinyl chloride resin, aliphatic dicarboxylate, and plasticizer, and may optionally include additives other than vinyl chloride resin, aliphatic dicarboxylate, and plasticizer.

[0048] In addition, the vinyl chloride resin molded body is formed by molding a vinyl chloride resin composition, so the mass ratio of each compounding component in the vinyl chloride resin molded body is usually the same as the mass ratio of each compounding component in the vinyl chloride resin composition.

[0049] <<Vinyl Chloride Resin>>

[0050] As a vinyl chloride resin, granular vinyl chloride resin is typically used. Furthermore, as a vinyl chloride resin, it can contain, for example, one or more types of vinyl chloride resin particles, and can also arbitrarily contain one or more types of vinyl chloride resin microparticles. Preferably, the vinyl chloride resin contains at least vinyl chloride resin particles, and more preferably, it contains both vinyl chloride resin particles and vinyl chloride resin microparticles.

[0051] Moreover, vinyl chloride resin can be manufactured using any of the previously known manufacturing methods, such as suspension polymerization, emulsion polymerization, solution polymerization, and bulk polymerization.

[0052] In addition, in this specification, "resin particles" refers to particles with a diameter of 30 μm or larger, and "resin microparticles" refers to particles with a diameter of less than 30 μm.

[0053] Furthermore, in addition to homopolymers composed of vinyl chloride monomer units, vinyl chloride copolymers containing at least 50% by mass, and more preferably at least 70% by mass, of vinyl chloride monomer units can be cited as examples of vinyl chloride copolymers. Moreover, as specific examples of monomers (comonomers) capable of copolymerizing with vinyl chloride monomers that can constitute vinyl chloride copolymers, monomers described in International Publication No. 2016 / 098344 can be used. Furthermore, these components can be used individually or in combination of two or more in any ratio.

[0054] [Vinyl chloride resin granules]

[0055] In vinyl chloride resin compositions, vinyl chloride resin particles typically function as the matrix resin (substrate). Furthermore, vinyl chloride resin particles are preferably manufactured via suspension polymerization.

[0056] -Average Degree of Polymerization-

[0057] Furthermore, the average degree of polymerization of the vinyl chloride resin constituting the vinyl chloride resin particles is preferably 800 or more, more preferably 1000 or more, more preferably 5000 or less, more preferably 3000 or less, and even more preferably 2800 or less. If the average degree of polymerization of the vinyl chloride resin constituting the vinyl chloride resin particles is 800 or more, it ensures that the physical strength of the vinyl chloride resin molded body formed using the vinyl chloride resin composition is sufficiently high, and it can improve, for example, tensile properties, particularly elongation at break. Moreover, vinyl chloride resin molded bodies with good elongation at break are preferably used as automotive interior materials, such as the surface of an automotive dashboard, which exhibits excellent ductility and will not scatter fragments during airbag inflation and deployment, but rather break according to design. On the other hand, if the average degree of polymerization of the vinyl chloride resin constituting the vinyl chloride resin particles is 5000 or less, it can improve the meltability of the vinyl chloride resin composition and improve the surface smoothness of the vinyl chloride resin molded body formed using this composition.

[0058] Furthermore, the average degree of polymerization of the vinyl chloride resin constituting the vinyl chloride resin particles can be above 1400, above 1500, or above 1600. Alternatively, it can be below 1600, below 1500, or below 1400.

[0059] In addition, in this specification, the "average degree of polymerization" can be determined according to JIS K6720-2.

[0060] -Average particle size-

[0061] Furthermore, the average particle size of the vinyl chloride resin particles is typically 30 μm or more, preferably 50 μm or more, more preferably 100 μm or more, more preferably 500 μm or less, and even more preferably 200 μm or less. If the average particle size of the vinyl chloride resin particles is 30 μm or more, the powder flowability of the vinyl chloride resin composition can be improved. On the other hand, if the average particle size of the vinyl chloride resin particles is 500 μm or less, the meltability of the vinyl chloride resin composition can be improved, and the surface smoothness of the vinyl chloride resin molded articles formed using this vinyl chloride resin composition can be improved.

[0062] In addition, in this specification, the "average particle size" can be determined in the form of volume average particle size by laser diffraction according to JIS Z8825.

[0063] -Contains proportion-

[0064] Furthermore, the content of vinyl chloride resin particles in the vinyl chloride resin is preferably 70% by mass or more, more preferably 80% by mass or more, and can be 100% by mass, preferably 95% by mass or less, and more preferably 90% by mass or less. If the content of vinyl chloride resin particles in the vinyl chloride resin is 70% by mass or more, it ensures that the physical strength of the vinyl chloride resin molded article formed using the vinyl chloride resin composition is sufficiently high, and it can improve the tensile elongation. On the other hand, if the content of vinyl chloride resin particles in the vinyl chloride resin is 95% by mass or less, it can improve the powder flowability of the vinyl chloride resin composition.

[0065] [Vinyl chloride resin microparticles]

[0066] In vinyl chloride resin compositions, vinyl chloride resin microparticles typically function as a separating agent (powder flowability improver). Furthermore, vinyl chloride resin microparticles are preferably manufactured via emulsion polymerization.

[0067] -Average Degree of Polymerization-

[0068] Furthermore, the average degree of polymerization of the vinyl chloride resin constituting the vinyl chloride resin microparticles is preferably 500 or more, more preferably 700 or more, more preferably 2600 or less, and even more preferably 2400 or less. If the average degree of polymerization of the vinyl chloride resin constituting the vinyl chloride resin microparticles as a separating agent is 500 or more, the powder flowability of the vinyl chloride resin composition can be improved, and the tensile elongation of the vinyl chloride resin molded article formed using the vinyl chloride resin composition can be improved. On the other hand, if the average degree of polymerization of the vinyl chloride resin constituting the vinyl chloride resin microparticles is 2600 or less, the meltability of the vinyl chloride resin composition can be improved, and the surface smoothness of the vinyl chloride resin molded article formed using the vinyl chloride resin composition can be improved.

[0069] -Average particle size-

[0070] Furthermore, the average particle size of the vinyl chloride resin particles is typically less than 30 μm, preferably less than 10 μm, more preferably less than 5 μm, more preferably more than 0.1 μm, and even more preferably more than 1 μm. If the average particle size of the vinyl chloride resin particles is 0.1 μm or more, for example, the size of the separating agent will not be excessively reduced, and the powder flowability of the vinyl chloride resin composition can be improved. On the other hand, if the average particle size of the vinyl chloride resin particles is less than 30 μm, the meltability of the vinyl chloride resin composition can be improved, and the surface smoothness of the formed vinyl chloride resin molded article can be improved.

[0071] [Contains percentage]

[0072] Furthermore, the content of vinyl chloride resin particles in the vinyl chloride resin can be 0% by mass, preferably 5% by mass or more, more preferably 10% by mass or more, preferably 30% by mass or less, and more preferably 20% by mass or less. If the content of vinyl chloride resin particles in the vinyl chloride resin is 5% by mass or more, the powder flowability of the vinyl chloride resin composition can be improved. On the other hand, if the content of vinyl chloride resin particles in the vinyl chloride resin is 30% by mass or less, the physical strength of the vinyl chloride resin molded article formed using the vinyl chloride resin composition can be improved.

[0073] <Aliphatic dicarboxylate>

[0074] In the laminate of the present invention, as described above, the aliphatic dicarboxylate is a component capable of inhibiting discoloration of the vinyl chloride resin molded article under high temperature conditions. Furthermore, the aliphatic dicarboxylate is also a component that functions as a powder flowability improver for the vinyl chloride resin composition when manufacturing vinyl chloride resin molded articles from the vinyl chloride resin composition.

[0075] In addition, aliphatic dicarboxylates can be used alone or in combination of two or more in any ratio.

[0076] Here, there is no particular limitation as long as the aliphatic dicarboxylic acid is in the form of a salt. Preferred salt forms include sodium salts, potassium salts, and calcium salts, among which sodium salts are particularly preferred from the viewpoint of further suppressing discoloration of vinyl chloride resin molded articles under high temperature conditions.

[0077] Furthermore, aliphatic dicarboxylic acids must be used in salt form, specifically as aliphatic dicarboxylic acid salts. If aliphatic dicarboxylic acids are used instead of aliphatic dicarboxylic acid salts, discoloration under high-temperature conditions cannot be adequately suppressed for the vinyl chloride resin molded parts that constitute the laminate.

[0078] Furthermore, the aliphatic dicarboxylic acid constituting the aliphatic dicarboxylic acid salt is not particularly limited as long as it is an aliphatic compound having two carboxylic acid groups. From the viewpoint of improving the flowability of the vinyl chloride resin composition while further suppressing discoloration of the vinyl chloride resin molded article under high temperature conditions, examples such as maleic acid, malonic acid, succinic acid, adipic acid, and sebacic acid are preferred. Moreover, among these, maleic acid is particularly preferred from the viewpoint of further suppressing discoloration of the vinyl chloride resin molded article under high temperature conditions.

[0079] Furthermore, in the laminate of the present invention, from the viewpoint of improving the flowability of the vinyl chloride resin composition while further suppressing discoloration of the vinyl chloride resin molded article under high temperature conditions, the aliphatic dicarboxylic acid salt is preferably a compound represented by the formula: NaOOC-R-COONa (where R is an aliphatic group with 1 or more carbon atoms and 8 or fewer), more preferably disodium maleate, disodium malonate, disodium succinate, disodium adipate, and disodium sebacic acid. Moreover, among these, from the viewpoint of further suppressing discoloration of the vinyl chloride resin molded article under high temperature conditions, disodium maleate is particularly preferred.

[0080] From the viewpoint of improving the fluidity of the vinyl chloride resin composition while further suppressing the discoloration of the vinyl chloride resin molded article under high temperature conditions, the content of aliphatic dicarboxylate in the vinyl chloride resin composition is preferably 0.30 parts by mass or more, more preferably 0.40 parts by mass or more, even more preferably 2.00 parts by mass or more, preferably 8.00 parts by mass or less, and more preferably 7.00 parts by mass or less, relative to 100 parts by mass of vinyl chloride resin.

[0081] Furthermore, when using disodium maleate as an aliphatic dicarboxylate, from the viewpoint of further suppressing discoloration of the vinyl chloride resin molded article under high temperature conditions, the content of disodium maleate in the vinyl chloride resin composition is preferably 0.30 parts by weight or more, more preferably 0.40 parts by weight or more, even more preferably 1.00 parts by weight or more, even more preferably 2.00 parts by weight or more, preferably 8.00 parts by weight or less, more preferably 7.00 parts by weight or less, even more preferably 5.00 parts by weight or less, even more preferably 4.00 parts by weight or less, and particularly preferably 3.00 parts by weight or less.

[0082] <Plasticizers>

[0083] Plasticizers are components that impart softness to vinyl chloride resin molded articles formed using vinyl chloride resin compositions. Furthermore, by using plasticizers in vinyl chloride resin compositions, the meltability of the vinyl chloride resin composition is improved, thus facilitating the molding of vinyl chloride resin articles (especially powder molding) and enhancing the surface smoothness of the formed vinyl chloride resin molded articles.

[0084] In addition, plasticizers can be used alone or in combination of two or more in any ratio.

[0085] Here, the content of plasticizer in the vinyl chloride resin composition is preferably 50 parts by weight or more, more preferably 75 parts by weight or more, further preferably 80 parts by weight or more, even more preferably 85 parts by weight or more, particularly preferably 90 parts by weight or more, preferably 200 parts by weight or less, more preferably 185 parts by weight or less, and even more preferably 150 parts by weight or less, relative to 100 parts by weight of vinyl chloride resin. If the content of plasticizer in the vinyl chloride resin composition is 50 parts by weight or more relative to 100 parts by weight of vinyl chloride resin, the meltability of the vinyl chloride resin composition can be sufficiently improved, and sufficient softness can be imparted to the formed vinyl chloride resin molded body. Furthermore, if the content of plasticizer in the vinyl chloride resin composition is 50 parts by weight or more relative to 100 parts by weight of vinyl chloride resin, the powder flowability of the vinyl chloride resin composition can be improved. On the other hand, if the content of plasticizer in the vinyl chloride resin composition is 200 parts by weight or less relative to 100 parts by weight of vinyl chloride resin, the lightfastness of the formed vinyl chloride resin molded body can be improved.

[0086] Here, the vinyl chloride resin composition preferably contains at least a polyester containing structural units derived from dioxic acid and structural units derived from polyols as a plasticizer, and more preferably contains both the polyester and other plasticizers (hereinafter referred to as "other plasticizers").

[0087] <<Polyester>>

[0088] As mentioned above, polyester contains structural units derived from dioxic acid and structural units derived from polyols.

[0089] By including the aforementioned polyester as a plasticizer, the vinyl chloride resin composition exhibits excellent melt properties. Furthermore, the polyester improves the powder flowability of the vinyl chloride resin composition and enhances the lightfastness and heat shrinkage resistance of the formed vinyl chloride resin molded articles.

[0090] [composition]

[0091] Furthermore, the polyester preferably contains structural units derived from 2-methyl-1,3-propanediol as structural units derived from polyols. Alternatively, the polyester may also contain structural units derived from polyols other than 2-methyl-1,3-propanediol (hereinafter sometimes referred to as "other polyols") as structural units derived from polyols.

[0092] When the total amount of structural units from polyols contained in the polyester is set to 100 mol%, the proportion of structural units from 2-methyl-1,3-propanediol among the structural units from polyols is preferably greater than 70 mol%, more preferably 80 mol% or more, further preferably 90 mol% or more, and even more preferably 95 mol% or more. If the proportion of structural units from 2-methyl-1,3-propanediol in the total amount of structural units from polyols contained in the polyester is greater than 70%, the melt properties and powder flowability of the vinyl chloride resin composition can be sufficiently improved, and the lightfastness of the formed vinyl chloride resin molded article can be sufficiently improved.

[0093] Furthermore, from the viewpoint of improving the melt properties and powder flowability of the vinyl chloride resin composition, as well as the light resistance of the formed vinyl chloride resin molded article, when the total amount of structural units from polyols contained in the polyester is set to 100 mol%, the content of structural units from 2-methyl-1,3-propanediol among the structural units from polyols is particularly preferably 100 mol%. That is, the polyester particularly preferably contains only structural units from 2-methyl-1,3-propanediol as structural units from polyols.

[0094] Examples of polyols other than 2-methyl-1,3-propanediol that can form structural units derived from other polyols in polyesters include 1,2-propanediol, 1,2-butanediol, 1,3-butanediol, 1,4-butanediol, 2,2-dimethyl-1,3-propanediol, and 3-methyl-1,5-pentanediol.

[0095] When the total amount of structural units derived from polyols contained in the polyester is set to 100 mol%, the proportion of structural units derived from other polyols among the structural units derived from polyols is preferably less than 30 mol%, more preferably less than 20 mol%, further preferably less than 10 mol%, and even more preferably less than 5 mol%. If the proportion of structural units derived from other polyols in the total amount of structural units derived from polyols contained in the polyester is less than 30 mol%, the melt properties and powder flowability of the vinyl chloride resin composition can be further improved, and the lightfastness of the formed vinyl chloride resin molded article can be further improved.

[0096] Furthermore, from the viewpoint of improving the melt properties and powder flowability of the vinyl chloride resin composition, as well as the light resistance of the formed vinyl chloride resin molded article, when the total amount of structural units from polyols contained in the polyester is set to 100 mol%, the content of structural units from other polyols among the structural units from polyols is particularly preferably 0 mol%. That is, the polyester is particularly preferably free of structural units from polyols other than 2-methyl-1,3-propanediol as structural units from polyols.

[0097] Furthermore, the polyester may contain structural units derived from polycarboxylic acids other than adipic acid as structural units derived from polycarboxylic acids. The proportion of adipic acid structural units in the total amount of polycarboxylic acid structural units in the polyester is preferably 50 mol% or more, more preferably 80 mol% or more, and particularly preferably 100 mol%. That is, the polyester particularly preferably contains only adipic acid structural units as structural units derived from polycarboxylic acids.

[0098] [Manufacturing Method]

[0099] Here, the aforementioned polyester is not particularly limited and can be obtained by polycondensation of adipic acid and a polyol. Furthermore, the polycondensation can be carried out in the presence of a catalyst. Additionally, the polycondensation can be carried out using an alcohol and / or a monocarboxylic acid as a terminating agent. Moreover, the polycondensation of adipic acid and the polyol, and the termination reaction of the resulting polycondensate with the terminating agent, can be carried out simultaneously or separately. Furthermore, the product obtained after polycondensation and the termination reaction can be subjected to post-treatment such as distillation. Moreover, the reaction conditions for polycondensation, including the monomers adipic acid and polyol, and the amounts of catalyst and terminating agent used, can be those known to be applicable.

[0100] In addition, commercially available products can be used as the aforementioned polyester.

[0101] There are no particular limitations on the catalysts used in polycondensation reactions; examples include dibutyltin oxide and tetraalkyl titanate.

[0102] In addition, examples of alcohols that can be used as terminal terminating components include methanol, ethanol, propanol, isopropanol, butanol, isobutanol, pentanol, hexanol, isohexanol, heptanol, isoheptanol, octanol, isooctanol, 2-ethylhexanol, nonanol, isononol, decanol, isodecanol, undecanol, isoundecanol, dodecanol, tridecanol, isotridecanol, tetradecanol, pentadecanol, hexadecanol, heptadecanol, octadecanol, cellosol, carbitol, phenol, nonylphenol, benzyl alcohol, and mixtures thereof.

[0103] Furthermore, examples of monocarboxylic acids that can be used as terminal terminating components include acetic acid, propionic acid, butyric acid, isobutyric acid, valeric acid, pentanoic acid, hexanoic acid, heptanoic acid, octanoic acid, 2-ethylhexanoic acid, nonanoic acid, decanoic acid, undecanoic acid, lauric acid, tridecanoic acid, tetradecanoic acid, pentadecanoic acid, palmitic acid, heptadecanoic acid, stearic acid, benzoic acid, and mixtures thereof.

[0104] 2-Ethylhexanol is preferred as the terminal terminating component.

[0105] [Physical properties, etc.]

[0106] Furthermore, the weight-average molecular weight of the polyester is preferably 1,000 or more, more preferably 2,000 or more, even more preferably 3,000 or more, preferably 10,000 or less, and more preferably 7,000 or less.

[0107] In addition, in this specification, the "weight-average molecular weight" of the polyester can be determined in the form of a polystyrene equivalent by gel permeation chromatography (GPC) using tetrahydrofuran as a solvent.

[0108] In addition, the acid value of the polyester is preferably 0.5 mg KOH / g or higher and 2 mg KOH / g or lower.

[0109] Furthermore, the hydroxyl value of the polyester is preferably 30 mg KOH / g or less, more preferably 10 mg KOH / g or less, and even more preferably 7 mg KOH / g or less.

[0110] In addition, in this specification, the “acid value” and “hydroxyl value” of the polyester can be determined using the method according to JIS K0070.

[0111] Furthermore, the viscosity of the polyester is preferably 500 mPa·s or more, more preferably 1000 mPa·s or more, more preferably 8000 mPa·s or less, more preferably 5000 mPa·s or less, and even more preferably 3000 mPa·s or less.

[0112] In addition, in this specification, the “viscosity” of the polyester can be measured at a temperature of 23°C according to JIS Z8803.

[0113] [Content, etc.]

[0114] The polyester content in the vinyl chloride resin composition is preferably greater than 30 parts by weight, more preferably 50 parts by weight or more, further preferably 70 parts by weight or more, even more preferably 80 parts by weight or more, particularly preferably 85 parts by weight or more, preferably less than 200 parts by weight, more preferably less than 150 parts by weight, and even more preferably less than 140 parts by weight. If the polyester content in the vinyl chloride resin composition is greater than 30 parts by weight relative to 100 parts by weight of vinyl chloride resin, the melt properties and powder flowability of the vinyl chloride resin composition, as well as the lightfastness and heat shrinkage resistance of the formed vinyl chloride resin molded article, can be improved. On the other hand, if the polyester content in the vinyl chloride resin composition is less than 200 parts by weight relative to 100 parts by weight of vinyl chloride resin, the lightfastness of the formed vinyl chloride resin molded article can be improved.

[0115] Based on 100% by mass of the total plasticizer, the polyester content in the plasticizer is preferably 50% by mass or more, more preferably 65% ​​by mass or more, further preferably 90% by mass or more, even more preferably 93% by mass or more, particularly preferably 95% by mass or more, and can be 100% by mass or less, preferably 99% by mass or less, more preferably 98% by mass or less, and even more preferably 97% by mass or less. If the polyester content in the plasticizer is 50% by mass or more, the melt flowability and powder flowability of the vinyl chloride resin composition, as well as the light resistance and heat shrinkage resistance of the formed vinyl chloride resin molded article, can be improved. On the other hand, if the polyester content in the plasticizer is 99% by mass or less, the light resistance of the formed vinyl chloride resin molded article can be improved.

[0116] <<Other Plasticizers>>

[0117] The content of other plasticizers in the vinyl chloride resin composition, relative to 100 parts by weight of vinyl chloride resin, can be 0 parts by weight or more, preferably 0.5 parts by weight or more, more preferably 1 part by weight or more, further preferably 1.5 parts by weight or more, even more preferably 2 parts by weight or more, preferably 40 parts by weight or less, more preferably 35 parts by weight or less, even more preferably 20 parts by weight or less, even more preferably 10 parts by weight or less, and particularly preferably 7 parts by weight or less. If the content of other plasticizers in the vinyl chloride resin composition is 0.5 parts by weight or more relative to 100 parts by weight of vinyl chloride resin, the softness of the formed vinyl chloride resin molded article can be improved. On the other hand, if the content of other plasticizers in the vinyl chloride resin composition is 40 parts by weight or less, the powder flowability of the vinyl chloride resin composition can be improved.

[0118] Furthermore, based on 100% by mass of the total plasticizer, the content of other plasticizers in the plasticizer can be 0% by mass or more, preferably 1% by mass or more, more preferably 2% by mass or more, further preferably 3% by mass or more, even more preferably 4.2% by mass or more, preferably 50% by mass or less, more preferably 35% by mass or less, even more preferably 10% by mass or less, even more preferably 7% by mass or less, and particularly preferably 5% by mass or less. If the content of other plasticizers in the plasticizer is 1% by mass or more, the softness of the formed vinyl chloride resin molded body can be further improved. On the other hand, if the content of other plasticizers in the plasticizer is 50% by mass or less, the powder flowability of the vinyl chloride resin composition can be improved.

[0119] Other plasticizers include, for example, plasticizers other than the polyesters described in International Publication No. 2016 / 098344.

[0120] More specifically, trimellitic esters and epoxidized vegetable oils can be used as other plasticizers, with epoxidized vegetable oils being preferred.

[0121] [Epoxidized Vegetable Oil]

[0122] Epoxidized vegetable oils can include, for example, epoxidized soybean oil and epoxidized linseed oil. Among these, from the viewpoint of improving the tensile properties of the formed vinyl chloride resin molded articles at low temperatures, epoxidized soybean oil is preferred as the epoxidized vegetable oil.

[0123] The content of epoxidized vegetable oil in the vinyl chloride resin composition is preferably 2 parts by weight or more and 7 parts by weight or less relative to 100 parts by weight of vinyl chloride resin. If the content of epoxidized vegetable oil in the vinyl chloride resin composition is within the above range, the tensile properties of the formed vinyl chloride resin molded article at low temperature can be improved.

[0124] The content of epoxidized vegetable oil in the plasticizer is preferably 1% by mass or less, more preferably 2% by mass or more, even more preferably 3% by mass or more, even more preferably 3.5% by mass or more, preferably 10% by mass or less, more preferably 7% by mass or less, and even more preferably 5% by mass or less. If the content of epoxidized vegetable oil in the plasticizer is within the above range, the tensile properties of the formed vinyl chloride resin molded article at low temperature can be improved.

[0125] <Additives>

[0126] In addition to the above-mentioned components, the vinyl chloride resin composition of the present invention may also contain various additives. As additives, there are no particular limitations, but examples include: lubricants; perchloric acid-treated hydrotalcite, zeolite, β-diketone, fatty acid metal salts, bis(1,2,2,6,6-pentamethyl-4-piperidinyl)-[[3,5-bis(1,1-dimethylethyl)-4-hydroxyphenyl]methyl]butylmalonate (light stabilizer), 6-amino-1,3-dimethyluracil, etc.; release agents; other releasing agents besides the above-mentioned vinyl chloride resin particles; impact resistance modifiers; perchloric acid compounds other than perchloric acid-treated hydrotalcite (sodium perchlorate, potassium perchlorate, etc.); antioxidants; mildew inhibitors; flame retardants; antistatic agents; fillers; foaming agents; pigments, etc.

[0127] Furthermore, as the additives that can be included in the vinyl chloride resin composition of the present invention, additives such as those described in International Publication No. 2016 / 098344 can be used, and their preferred contents can also be the same.

[0128] <Preparation Method of Vinyl Chloride Resin Composition>

[0129] The vinyl chloride resin composition used to prepare vinyl chloride resin molded articles can be prepared by mixing the above-mentioned components.

[0130] Here, the mixing method for vinyl chloride resin, aliphatic dicarboxylate, plasticizer, and various additives further formulated as needed is not particularly limited. Examples include, for instance, dry mixing of all components except the release agent (containing vinyl chloride resin particles), followed by adding the release agent and mixing again. Here, a Henschel mixer is preferably used for dry mixing. Furthermore, the temperature during dry mixing is not particularly limited, but is preferably 50°C or higher, more preferably 70°C or higher, and most preferably 200°C or lower.

[0131] <Foamed Polyurethane Molded Body>

[0132] There are no particular limitations on the foamed polyurethane molded body; any known foamed polyurethane molded body obtained by polymerizing isocyanates and polyols through reaction and foaming polyurethane can be used.

[0133] There are no particular limitations on isocyanates and polyols; known substances can be used. Furthermore, there are no particular limitations on the polymerization and foaming methods; known methods can be used. Additionally, there are no particular limitations on the polymerization catalysts used in the reaction of isocyanates and polyols; examples include amines such as triethylenediamine, triethanolamine, and triethylamine.

[0134] (Manufacturing method of laminated bodies)

[0135] The laminate of the present invention is not particularly limited and can be manufactured using the manufacturing method of the laminate of the present invention.

[0136] The method for manufacturing the laminate of the present invention includes: a step of molding a vinyl chloride resin composition comprising vinyl chloride resin, an aliphatic dicarboxylate, and a plasticizer to obtain a vinyl chloride resin molded body (molded body forming step); and a step of laminating a foamed polyurethane molded body onto the surface of the vinyl chloride resin molded body obtained in the molded body forming step to obtain a laminate of adjacent layers of the vinyl chloride resin molded body and the foamed polyurethane molded body (laminated body forming step). Furthermore, the method for manufacturing the laminate of the present invention may arbitrarily include steps other than the molded body forming step and the laminate forming step.

[0137] Furthermore, according to the manufacturing method of the laminate of the present invention, it is possible to efficiently produce a laminate that suppresses discoloration of the vinyl chloride resin molded body under high temperature conditions.

[0138] <Molded body forming process>

[0139] In the molding process, a vinyl chloride resin composition comprising at least vinyl chloride resin, aliphatic dicarboxylate, and plasticizer, and optionally additives, is molded to obtain a vinyl chloride resin molded body. Here, "vinyl chloride resin," "aliphatic dicarboxylate," "plasticizer," and "additives" are the same as those described in the "Laminated Body" section, and their preferred examples, preferred contents, etc., are also the same as those described in the "Laminated Body" section.

[0140] There are no particular limitations on the molding method for producing vinyl chloride resin molded articles by molding a vinyl chloride resin composition, and known molding methods can be used. Moreover, as a molding method, powder slush molding is preferred, for example, from the viewpoint of easily obtaining vinyl chloride resin molded articles that can be well used as automotive interior materials such as dashboard covers.

[0141] Here, when forming a vinyl chloride resin molded body by powder slush molding, there is no particular limitation on the mold temperature during powder slush molding, but it is preferably 200°C or higher, more preferably 220°C or higher, more preferably 300°C or lower, and more preferably 280°C or lower.

[0142] Furthermore, there are no particular limitations in manufacturing the vinyl chloride resin molded body, and methods such as the following can be used: The vinyl chloride resin composition of the present invention is sprinkled onto a mold within the aforementioned temperature range, left for 5 seconds to 30 seconds, excess vinyl chloride resin composition is shaken off, and then left at any temperature for 30 seconds to 3 minutes. The mold is then cooled to 10°C to 60°C, and the resulting vinyl chloride resin molded body is demolded from the mold. A sheet-like molded body shaped according to the mold is then obtained.

[0143] <Laminated body formation process>

[0144] In the laminate formation process, a polyurethane foam molded body is laminated (lined) on the surface of the vinyl chloride resin molded body obtained in the molding process, resulting in a laminate of the vinyl chloride resin molded body and the polyurethane foam molded body.

[0145] There are no particular limitations on the lamination method of the vinyl chloride resin molded body and the foamed polyurethane molded body, and the following methods can be used, for example: (1) preparing the vinyl chloride resin molded body and the foamed polyurethane molded body separately and then bonding them together using heat fusion, heat bonding or known adhesives; (2) reacting isocyanates and polyols, which are raw materials for the foamed polyurethane molded body, with the vinyl chloride resin molded body to polymerize and foam the polyurethane, thereby directly forming the foamed polyurethane molded body on the vinyl chloride resin molded body. Among these, the latter method (2) is preferred from the viewpoint of simple process and the viewpoint that the vinyl chloride resin molded body and the foamed polyurethane molded body can be firmly bonded even when a laminate of various shapes is obtained.

[0146] Example

[0147] The present invention will now be specifically described based on embodiments, but the present invention is not limited to these embodiments. Furthermore, in the following description, unless otherwise specified, "%" and "parts" refer to quantities based on mass.

[0148] Furthermore, the powder flowability of the vinyl chloride resin composition and the color change suppression of the vinyl chloride resin molded body constituting the laminate under high temperature conditions were evaluated using the following method.

[0149] <Powder Flowability>

[0150] The vinyl chloride resin compositions obtained in the examples and comparative examples were poured from the funnel of a powder testing machine (manufactured by Nippon Oil Testing Instruments Industry, model "TESTERTYPE 6721") into a 100cc brass hopper, thereby filling the hopper with the vinyl chloride resin composition. Then, the vinyl chloride resin composition was poured again from the hopper into the funnel, allowing it to fall onto a flat plate. The time (in seconds) until all the vinyl chloride resin composition had fallen was measured and recorded as the falling seconds. The shorter the falling seconds, the better the powder flowability of the vinyl chloride resin composition.

[0151] <Color Change Inhibition>

[0152] The hue of the vinyl chloride resin molded body side surface (textured surface) of the laminates obtained in the examples and comparative examples was measured using a spectrophotometer (manufactured by Konica Minolta Co., Ltd., model "CM-700d"). More specifically, the entire textured surface was divided into 9 parts, and a total of 9 points were measured at the center of each part. The resulting 9 E values ​​were then analyzed. * The average value is set to E0. * .

[0153] Next, the laminate was subjected to a high-temperature treatment at 120°C for 400 hours in a Gill oven. The laminate after the high-temperature treatment was then subjected to colorimetric measurement in the same manner as described above, and the resulting E values ​​were... * The average value is set to E1 * .

[0154] Then, according to the formula: ΔE * =E1 * -E0 * Calculate ΔE * ΔE * The smaller the value, the more the discoloration of the vinyl chloride resin molded body is suppressed under high temperature conditions.

[0155] (Preparation of polyester A containing structural units derived from adipic acid and structural units derived from polyols)

[0156] Adipic acid (as a polycarboxylic acid), 2-methyl-1,3-propanediol (as a polyol), and 2-ethylhexanol (as a terminator / terminant) were added to a reaction vessel. Tetraisopropyl titanate was added as a catalyst, and an appropriate amount of solvent was added. The mixture was stirred and heated. The byproduct water was removed under normal and reduced pressure. Finally, the temperature was raised to 220–230 °C to terminate the dehydration condensation reaction, yielding polyester A (viscosity: 2800 mPa·s, weight-average molecular weight: 4200, acid value: 1.0 mg KOH / g, hydroxyl value: 5.5 mg KOH / g) with 2-ethylhexyloxy groups at the end.

[0157] (Example 1)

[0158] <Preparation of Vinyl Chloride Resin Compositions>

[0159] In the formulation shown in Table 1, all components except the plasticizer (polyester A and epoxidized soybean oil) and the vinyl chloride resin microparticles as a release agent were added to a Henschel mixer and mixed. Then, when the temperature of the mixture reached 80°C, all of the aforementioned plasticizer was added, allowing it to dry completely (meaning the plasticizer was absorbed by the vinyl chloride resin particles, resulting in a dry mixture). Then, when the temperature of the dried mixture cooled to below 70°C, the vinyl chloride resin microparticles as a release agent were added to prepare the vinyl chloride resin composition.

[0160] The powder flowability of the obtained vinyl chloride resin composition was evaluated. The results are shown in Table 3.

[0161] <Molded body forming process>

[0162] The obtained vinyl chloride resin composition was sprinkled onto a textured mold heated to 250°C. After allowing it to melt for an arbitrary time, excess vinyl chloride resin composition was shaken off. Then, the textured mold containing the vinyl chloride resin composition was placed in an oven at 200°C and allowed to stand for 60 seconds. After this period, the mold was cooled with cooling water. When the mold temperature cooled to 40°C, a vinyl chloride resin molded body (vinyl chloride resin molded sheet) measuring 150mm × 200mm × 1mm was demolded from the mold.

[0163] <Laminated body formation process>

[0164] Two pieces of the obtained vinyl chloride resin molded body are laid in a 200mm×300mm×10mm mold with the textured side facing down and the two pieces not overlapping each other.

[0165] On the other hand, a polyol mixture was prepared by mixing 50 parts of a propylene glycol PO (propylene oxide)·EO (ethylene oxide) block adduct (hydroxyl value: 28 mg KOH / g, terminal EO unit content: 10%, internal EO unit content: 4%), 50 parts of a glycerol PO·EO block adduct (hydroxyl value: 21 mg KOH / g, terminal EO unit content: 14%), 2.5 parts of water, 0.2 parts of a triethylenediamine ethylene glycol solution (manufactured by Tosoh Corporation, trade name "TEDA-L33"), 1.2 parts of triethanolamine, 0.5 parts of triethylamine, and 0.5 parts of a foam stabilizer (manufactured by Shin-Etsu Chemical Co., Ltd., trade name "F-122"). Furthermore, the obtained polyol mixture was mixed with polymethylene polyphenylene isocyanate (polymeric MDI) at an index of 98 to prepare a mixed solution. Next, the prepared mixture is injected onto two polyethylene resin molding sheets laid in the mold. Then, the mold is covered with a 200mm × 300mm × 10mm aluminum plate to seal it. After sealing the mold, it is left for 5 minutes, thereby forming a foamed polyurethane molded body (thickness: 9mm, density: 0.18g / cm³) within the metal mold. 3 A laminated body with a vinyl chloride resin molded body (thickness: 1 mm) as a lining.

[0166] The resulting laminate was removed from the mold, and the color discoloration inhibition of the vinyl chloride resin molded body under high temperature conditions was evaluated. The results are shown in Table 3.

[0167] (Examples 2-16, Comparative Example 1)

[0168] In preparing the vinyl chloride resin composition, the types and / or amounts of the compounding components used were varied as shown in Tables 1 and 2. Otherwise, the vinyl chloride resin composition, vinyl chloride molded body, and laminate were prepared in the same manner as in Example 1. Then, the evaluation was performed in the same manner as in Example 1. The results are shown in Tables 3 and 4.

[0169] [Table 1]

[0170]

[0171] [Table 2]

[0172]

[0173] [Table 3]

[0174]

[0175] [Table 4]

[0176]

[0177] 1) Manufactured by Shinichi Chloride Co., Ltd., product name "ZEST (registered trademark) 1700ZI" (prepared by suspension polymerization, average degree of polymerization: 1700, average particle size: 129μm).

[0178] 2) Manufactured by Shinichi Chloride Co., Ltd., product name "ZEST PQLTX" (prepared by emulsion polymerization, average degree of polymerization: 800, average particle size: 1.8μm)

[0179] 3) Manufactured by ADK CIZER Co., Ltd., product name "ADK CIZER (registered trademark) O-130S"

[0180] 4) Manufactured by Kyowa Chemical Industry Co., Ltd., product name "ALCAMIZER (registered trademark)"

[0181] 5) Manufactured by Mizusawa Chemical Industry Co., Ltd., product name "MIZUKALIZER (registered trademark) DS"

[0182] 6) Manufactured by Rezonak Co., Ltd., product name "Karenz (registered trademark) DK-1"

[0183] 7) Manufactured by BASF, product name "Tinuvin (registered trademark) 144", bis(1,2,2,6,6-pentamethyl-4-piperidinyl)-[[3,5-bis(1,1-dimethylethyl)-4-hydroxyphenyl]methyl]butylmalonate

[0184] 8) Sakai Chemical Industry Co., Ltd., product name "SAKAI SZ2000"

[0185] 9) Manufactured by Fujifilm and Wako Pure Chemical Industries, Ltd.

[0186] 10) Manufactured by ADK STAB Co., Ltd., product name "ADK STAB (registered trademark) LS-12"

[0187] 11) Manufactured by Daihatsu Seika Co., Ltd., product name "DA P-1050WHITE"

[0188] 12) Manufactured by Dainippon Seika Co., Ltd., product name "DAP-4720BLACK"

[0189] 13) Manufactured by Dainippon Seika Co., Ltd., product name "DAP-4446YELLOW"

[0190] 14) Made by Tokyo Chemical Industry Co., Ltd.

[0191] 15) Made by Tokyo Chemical Industry Co., Ltd.

[0192] 16) Made by Tokyo Chemical Industry Co., Ltd.

[0193] 17) Made by Tokyo Chemical Industry Co., Ltd.

[0194] 18) Made by Tokyo Chemical Industry Co., Ltd.

[0195] As shown in Tables 1-4, the laminates of Examples 1-16, which are obtained by laminating a vinyl chloride resin molded body made of a vinyl chloride resin composition containing vinyl chloride resin, aliphatic dicarboxylate and plasticizer and a foamed polyurethane molded body, can suppress the discoloration of the vinyl chloride resin molded body under high temperature conditions compared with Comparative Example 1.

[0196] Industrial availability

[0197] According to the present invention, a laminate of a vinyl chloride resin molded body and a foamed polyurethane molded body that suppresses discoloration of the vinyl chloride resin molded body under high temperature conditions can be provided, as well as a method for manufacturing the laminate.

Claims

1. A laminate comprising a vinyl chloride resin molded body and a foamed polyurethane molded body laminated adjacent to the vinyl chloride resin molded body, The vinyl chloride resin molded body is a molded body formed by molding a vinyl chloride resin composition containing vinyl chloride resin, aliphatic dicarboxylate, and plasticizer. The aliphatic dicarboxylate contains at least one selected from disodium maleate, disodium malonate, disodium succinate, disodium adipate, and disodium sebacic acid.

2. The laminated body according to claim 1, wherein, The content of the aliphatic dicarboxylate in the vinyl chloride resin composition is 0.30 parts by weight or more and 8.00 parts by weight or less relative to 100 parts by weight of the vinyl chloride resin.

3. The laminated body according to claim 1, wherein, The content of the plasticizer in the vinyl chloride resin composition is 50 parts by weight or more and 200 parts by weight or less relative to 100 parts by weight of the vinyl chloride resin.

4. The laminated body according to claim 1, wherein, The plasticizer comprises a polyester containing structural units derived from bisaccharide and structural units derived from polyols.

5. The laminate according to any one of claims 1 to 4, wherein, The laminate is used for automotive dashboards.

6. A method for manufacturing a laminate, comprising the following steps: The process of molding a vinyl chloride resin composition comprising vinyl chloride resin, an aliphatic dicarboxylate, and a plasticizer to obtain a vinyl chloride resin molded article; and The process of laminating a polyurethane foam molded body onto the surface of a vinyl chloride resin molded body to obtain a laminate consisting of adjacent layers of the vinyl chloride resin molded body and the polyurethane foam molded body. The aliphatic dicarboxylate contains at least one selected from disodium maleate, disodium malonate, disodium succinate, disodium adipate, and disodium sebacic acid.

7. The method for manufacturing a laminate according to claim 6, wherein, The content of the aliphatic dicarboxylate in the vinyl chloride resin composition is 0.30 parts by weight or more and 8.00 parts by weight or less relative to 100 parts by weight of the vinyl chloride resin.

8. The method for manufacturing a laminate according to claim 6, wherein, The content of the plasticizer in the vinyl chloride resin composition is 50 parts by weight or more and 200 parts by weight or less relative to 100 parts by weight of the vinyl chloride resin.

9. The method for manufacturing a laminate according to claim 6, wherein, The plasticizer comprises a polyester containing structural units derived from bisaccharide and structural units derived from polyols.

10. The method for manufacturing a laminate according to any one of claims 6 to 9, wherein, The vinyl chloride resin composition powder is slush molded to obtain the vinyl chloride resin molded body.

Citation Information

Patent Citations

  • Vinyl chloride resin composition, method for producing same, vinyl chloride resin molded article, method for producing same, and laminate

    WO2016098344A1

  • Vinyl chloride resin composition for powder molding, vinyl chloride resin molded article, and laminate

    WO2020090556A1

  • Vinyl chloride resin composition for powder molding, vinyl chloride resin molded article, and laminate

    CN112867592A

  • Vinyl chloride resin composition for powder molding

    JP1989065157A